PENERAPAN METODE QUANTUM TAHFIZ DALAM MENINGKATKAN HAFALAN AL-QUR’AN SANTRIWATI - Nuraini Nuraini; Alimron Alimron; Ahmad Syarifuddin (PAI RAFAH, 2022)
The purpose of this study is to determine the memorization of the Qur'an of female santri before the application of the Quantum Tahfiz method, 2. To determine the memorization of the Qur'an of female santri after the application of the Quantum Tahfiz method, 3. To determine the increase in memorization of the Qur'an of female santri before and after the application of the Quantum Tahfiz method. This type of research is quantitative and the research method used is the One-Group Pretest-Posttest experiment, the population in this study is 150 female students with a sample of 15 female students, data collection techniques using observation, tests, and documentation. Data analysis using the "t" test. The results of the analysis in this study are the memorization of the Qur'an before the application of the Quantum Tahfiz method obtained an average value of 29.4, which means it is classified in the medium category and the percentage level is smaller than after applying the Quantum Tahfiz method. After applying the Quantum Tahfiz method obtained an average value of 35.4, meaning that it was classified as a moderate category and the level of presentation was greater than before applying the Quantum Tahfiz method. Based on the results of calculations using the "t" test formula that to is greater than tt, namely 2.14 < 6.008 > 2.98, then the alternative hypothesis Ha is accepted and Ho is rejected, meaning that there is a significant increase in the memorization of the Qur'an of female santri at Pondok Pesantren Tahfizhul Qur'an Putri Al-Lathifiyyah Palembang after the application of the Quantum Tahfiz method.